2007
DOI: 10.1111/j.1365-2826.2007.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids, 11β‐Hydroxysteroid Dehydrogenase Isozymes and the Rabbit Choroid Plexus

Abstract: The epithelial cells of the choroid plexus (CP) are responsible for cerebrospinal fluid (CSF) secretion into the ventricles of the brain. The balance between CSF production and drainage, in part, facilitates a normal intracranial pressure. The secretion of Na(+) and anions by the CP creates an osmotic gradient driving water into the ventricles. This is opposite to classical Na(+) transporting tissues, such as the kidney, where Na(+) and water reabsorption is mediated by 11beta-hydroxysteroid dehydrogenase type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…We previously suggested that 11␤-HSD1 may influence ICP through the regulation of CSF homeostasis in a fashion analogous to that reported by our group in the ciliary body (22,23). In keeping with this, we have demonstrated 11␤-HSD1 immunoreactivity in the CSF secreting CP epithelial cells.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We previously suggested that 11␤-HSD1 may influence ICP through the regulation of CSF homeostasis in a fashion analogous to that reported by our group in the ciliary body (22,23). In keeping with this, we have demonstrated 11␤-HSD1 immunoreactivity in the CSF secreting CP epithelial cells.…”
Section: Resultssupporting
confidence: 72%
“…Here, cortisol generation by 11␤-HSD1 stimulates serum and glucocorticoid-regulated kinase (sgk) 1 to increase epithelium Na ϩ transport and aqueous humor production (22). Inhibition of 11␤-HSD1 lowers intraocular pressure (23). We suggest that, akin to the ocular ciliary body, in the CP CSF secretion may be regulated by 11␤-HSD1 (Fig.…”
mentioning
confidence: 99%
“…Although the mechanism by which steroids modulate CSF absorption is unknown, a putative mechanism exists for their effects on CSF production. The enzyme 11␤-hydroxysteroid dehydrogenase type 1 (11␤-HSD1) is highly expressed in choroid plexus (CP) epithelium, and despite being a bidirectional enzyme, its main activity is the reduction of inactive cortisone to cortisol (14). In addition, mineralocorticoid receptors are highly abundant in CP epithelium and are activated by cortisol and aldosterone with a similar affinity (15).…”
Section: Discussionmentioning
confidence: 99%
“…Two main targets of these theories are mineralocorticoid receptors and the enzyme 1β-hydroxysteroid dehydrogenase (11β-HSD). 24,25 Mineralocorticoid receptors have been identified in the choroid plexus (CP) epithelium and they function in a way similar to their role in the kidney, through activation of Na/K ATPase, altering the composition of CSF, while high GC levels are known to activate mineralocorticoid receptors. The enzyme 1β-hydroxysteroid dehydrogenase (11β-HSD) is also expressed in CP epithelium and its normal function is to activate cortisol from cortisone (11β-HSD1) or vice versa (11β-HSD2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%